2015
DOI: 10.1177/1745691615577701
|View full text |Cite
|
Sign up to set email alerts
|

One Century of Global IQ Gains

Abstract: The Flynn effect (rising intelligence test performance in the general population over time and generations) varies enigmatically across countries and intelligence domains; its substantive meaning and causes remain elusive. This first formal meta-analysis on the topic revealed worldwide IQ gains across more than one century (1909-2013), based on 271 independent samples, totaling almost 4 million participants, from 31 countries. Key findings include that IQ gains vary according to domain (estimated 0.41, 0.30, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(62 citation statements)
references
References 126 publications
5
57
0
Order By: Relevance
“…One limitation is that we did not evaluate term-born control children, but rather compared the distribution of cognitive outcomes in our cohort with standardized population-based normative means and standard deviations. Although population norms may change over time (Flynn effect)(54), such drift is most often towards higher scores on standardized tests of cognition. Thus, the magnitude of differences seen in our cohort is unlikely explained by modest drift in normative test performance.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation is that we did not evaluate term-born control children, but rather compared the distribution of cognitive outcomes in our cohort with standardized population-based normative means and standard deviations. Although population norms may change over time (Flynn effect)(54), such drift is most often towards higher scores on standardized tests of cognition. Thus, the magnitude of differences seen in our cohort is unlikely explained by modest drift in normative test performance.…”
Section: Discussionmentioning
confidence: 99%
“…In several countries large increases in fluid and crystallized intelligence have been documented from the 1930's into the late 20 th century. This phenomenon is dubbed the Flynn effect (Flynn, 1987) and has also been observed in several cross-temporal meta-analyses, including studies extending the effect into the 2010's (Pietschnig & Voracek, 2015;Raven, 2000;Trahan, Stuebing, Hiscock, & Fletcher, 2014). Further, as some have argued that there are multiple flavors or types of intelligence, beyond cognitive capacities that have typically been studied (Gardner, 2011;Sternberg, 1985), it is interesting to note that athletic performance in a wide variety of sports has increased considerably during the past century (Kaufman, 2013).…”
Section: Intelligencementioning
confidence: 76%
“…The results showed that IQ increased by approximately four points per decade from 1988 to 1997; however, from 1997 to 2009, average IQ scores declined by approximately two points per decade. Pietschnig and Voracek's () meta‐analysis of IQ gains across 31 countries also found that substantial gains were evident between 1909 and 2013; however, the strength of IQ gains decreased over time.…”
Section: Discussionmentioning
confidence: 94%